Aplikasi Filter KALMAN Pada Gerak Matra Longitudinal Pesawat Udara Boeing-747 - Syamsuar, Sayuti (Warta Penelitian Perhubungan, 2011)
Many of aircraft perfonnance became from the stability and control of flight test data analysis. This paper introduces the Kalman Filter analysis on the Boeing 747 data aircraft to knawn the output response if disturbance (as turbulence or noise) absence on the closed loop control system. We found the output response of the plant on algorithm Kalman Filter tend to the unstable conditions, but we don't knaw the response of the whole of closed loop diagram block control system of Boeing 747 aircraft.Keywords : aircraft control system, turbulence, Kalman Filter